Mechanical Thrombectomy in Ischemic Stroke Patients with Severe Pre-stroke Disability - Salwi, Sanjana (J Stroke Cerebrovasc Dis, 2020)
Frequency and outcomes of mechanical thrombectomy (MT) in clinical practice for patients with severe pre-stroke disability are largely unknown. In this case series, we aim to describe the disability make-up and outcomes of 33 patients with severe pre-stroke disability undergoing MT. Patients with a permanent, severe, pre-stroke disability (modified Rankin Score, mRS, 4–5) were identified from a prospectively-maintained database of consecutive, MT-treated, acute ischemic anterior circulation stroke patients at two comprehensive stroke centers in the United States. We present details on the cause of disability and socio-demographic status as well as procedural and functional outcomes. This study, despite the lack of inferential testing due to limited sample size, provides insight into demographics and outcomes of MT-treated patients with severe pre-stroke disability. Rate of return to functional baseline as well as rates of procedural success and complications were comparable to that reported in the literature for patients without any pre-existing disability.